Culture as an obstacle for entrepreneurship (2022)
This research was aimed to identify the main reasons why entrepreneurs in the city of Ibagué, who structure business ideas and participate in contests and/or calls, do not continue the entrepreneurial process until the creation of their companies. After applying the validated instrument (survey) to more than 100 students from the Universidad de Ibagué and expert advisers from the department of Tolima, made up of universities, entrepreneurs, and public–private institutions, with interests in entrepreneurship; it was possible to recognize that the main reason, why entrepreneurs generate ideas, but not companies, is the cultural factor. The foregoing is based on the fact that Tolima has been a quintessential agricultural department and this situation has contributed greatly to the fact that the entrepreneurial spirit has not been developed in people. Within the research results it was detected that in contrast with other cities of Colombia, like Manizales and Medellín, Ibagué has not been able to consolidate a solid entrepreneurial ecosystem due to the lack of coordination among private, public, and academic sectors, and on the other side, a majority of people from Ibagué do not have family support for the development of their initiatives, being fundamental components for the creation of enterprises. Among the recommendations proposed in the study is the construction of an entrepreneurial ecosystem, because it will allow the participation of the Triple Helix by providing opportunities to all entrepreneurs in the region; in addition, it is considered important that educational institutions, both schools and universities, promote the development of entrepreneurial skills and competencies in individuals involving their families.